Analisis Karakteristik Perjalanan dan Moda Transportasi Pelajar di Kota Padang untuk Mengurangi Angka Kecelakaan Lalulintas - Gusri Yaldi; Imelda M. Nur; Apwiddhal (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
Motorcyclists involved in 74% road traffic accidents (RTA) in Indonesia and the majority were students. WHO reported that 74% of RTA death victims were motorcyclists. This research aimed at analysing student trip and mode characteristics by using Revealed Preference survey. Majority of students were found using motorcycles due to travel time and cost. Average travel and waiting times are 18.5 and 0.1 minutes. Average travel cost varies between Rp.3750-Rp.4950. The ratio between students categorized as captive and choice users are 75%;25%. Majority of students depart before 07.00 AM and end their trips before 3 PM. In order to encourgae students to shift to public transport, the Trans Padang service is recommended to be integrated with parking facilities which is the direction of the future research.